The Effect of Vitamin D Supplementation on Symptoms of Depression in Patients with Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Putranto, Rudi; Harimurti, Kuntjoro; Setiati, Siti; Safitri, Eka Dian; Saldi, Siti Rizny F; Subekti, Imam; Nasrun, Martina Wiwie S; Shatri, Hamzah (Acta Medica Indonesiana, 2023)
Background: The effect of vitamin D supplementation on depressive symptoms in people with type 2 diabetes is still up for debate. The aim of this paper was to investigate the effect of vitamin D supplementation on symptoms of depression in type 2 diabetic patients. Methods: The protocol for this review has been registered in PROSPERO:CRD42021231713. Searching for literature was conducted using Pubmed, EBSCOhost, and EMBASE. Randomised controlled trials (RCTs) regarding vitamin D supplementation in type 2 diabetic patients with depression were retrieved through a systematic search. The outcome measured was a change in depressive symptoms evaluated with any validated rating scale. Independent data extraction was conducted, and the study quality was assessed. A meta-analysis was carried out to calculate the improvement in depressive symptoms in the group receiving vitamin D and the control group. The available evidence in RCTs was analysed using the PRISMA approach, and clinical significance was determined using the GRADE system. Risk of bias was assessed using the Cochrane Risk of Bias Tool. Results: Four RCTs were reviewed and three RCTs were meta-analysed. In two studies, vitamin D was statistically effective in improving depressive symptoms in type 2 diabetic patients. Three randomised controlled trials were included in the meta-analysis with 161 subjects using depression score as an outcome assessment. Vitamin D is significantly more effective than placebo (95% CI: -0.70 to - 0.08, p = 0.01). Conclusion: Vitamin D supplementation may improve the depressive symptoms in type 2 diabetic patients. Future research with different geographical areas and larger samples should be done to further assess the benefits.